Causal interaction between FDI, corruption and environmental quality in the MENA region - Wajdi Bardi; Mohamed Ali Hfaiedh (Economies, 2021)
The present work analyzes the impact of foreign direct investment (FDI) and corruption on the quality of the environment in the MENA region. Indeed, the magnitude of corruption and the quality of institutions are often cited as the main factors affecting the FDI inflow. Here, the Autoregressive Distributed Lag (ARDL) approach was used to examine data on a group of MENA countries from 1990 to 2016. Our findings verify the Environmental Kuznets Curve. Furthermore, the empirical estimates approve the "pollution haven" hypothesis, which postulates that the polluting industrial activities of developed countries shift to developing countries which have less stringent environmental regulations. Based on the study findings, we recommend greater awareness of the harmful effects of corruption among political and economic actors.
Keywords: 330; foreign direct investment; economic growth; pollution; corruption; Environmental Kuznets Curve; Autoregressive Distributed Lag